Three Early Islamic Stelae Found in the Malay Archipelago and Its Artistic Relation with the Eastern Islamic World - Ismail, Muhammad Uzair; Ahmad Zakaria , Ros Mahwati; Ramli, Zuliskandar (Journal of Al-Tamaddun, 2023)
This study examined the decorative elements present on three early Islamic stelae – the Champa Pillar (1035CE), Putri Makhdarah’s tombstone (1048CE) and Fatimah’s tombstone (1082CE) – which were found in the Malay Archipelago and dated to the eleventh century CE. These objects are of tremendous significance as they are the earliest Islamic evidence in Southeast Asia that indicates Muslim presence in the region. Regrettably, although is it acknowledged that one of the earliest cultural influences that spread towards the Malay Archipelago is Persian, the artistic dimensions of the stelae are rarely discussed in terms of its influence and connection with the eastern Islamic lands after the Muslim conquest in the seventh century CE. This is because previous studies are more concerned with the inscription and material from the archaeological, historical and palaeographic approach rather than art history. Therefore, this study adopted the art historical method where the analysis concerned the development and influence of the Islamic art in the region. Based on the analysis, it was discovered that these stelae have connections in terms of their artistic repertoire, format, type and context of certain motifs used with the ones found in the eastern Islamic lands, namely Iran and Transoxiana. This connection is particularly evident in the type of calligraphy used, involving round script and foliated Kufic, as well as the use of lamp motif (misbah) in mihrab images. Both have been found to be extensively used in Iran and Transoxiana for tombstones, gravestones, mausoleums, commemorative texts and Quranic manuscripts, contemporary with the development of Islamic art in the region. Hence, the findings from this analysis indicate that the source of Islamic decorative elements used by the Malays in their Islamic art stemmed from Iran and Transoxiana and was heavily rooted in the Turco-Persian influence since the coming of Islam to Southeast Asia.